Transformative Curriculum in Indonesian Higher Education: An Integrative Framework for Realizing University 4.0 - Khafido, Neneng; Permawati, Hesih; Susanti, Eni (Indonesian Journal of Education and Mathematical Science, 2026)
The transformation of higher education toward the University 4.0 paradigm demands fundamental changes in curriculum design that transcend conventional knowledge transmission. This article aims to analyze the components of transformative curriculum as an integrative learning framework in Indonesian higher education, encompassing learning orientation, learning materials, learning methods, and learning evaluation. The study employed a literature review method with a conceptual analysis approach applied to the Guide to Transformative Pedagogy for Lecturers (Ministry of Higher Education, Science and Technology, 2025), synthesized with Mezirow's transformative learning theory, Freire's critical pedagogy, and Ki Hadjar Dewantara's educational philosophy. The findings reveal that transformative curriculum comprises four interrelated components. Learning orientation focuses on developing critical consciousness through three levels of reflection: content reflection, process reflection, and premise reflection. Learning materials integrate three main pillars—inclusivity, sustainability, and social justice and anti-racism—contextualized within societal realities. Learning methods include the case-method, reflective discussion, simulation, project-based learning, and narrative inquiry, all of which emphasize the dialectic between reflection and action. Learning evaluation is qualitative, reflective, participatory, and narrative in nature, prioritizing the process of perspective transformation through reflective journals, transformative portfolios, action projects, and self- and peer-evaluation. Transformative curriculum provides an operational framework for higher education institutions to realize meaningful learning with social impact, aligned with the Impactful Higher Education (Diktisaintek Berdampak) policy and the Sustainable Development Goals.